2021
DOI: 10.1093/mnras/stab2685
|View full text |Cite
|
Sign up to set email alerts
|

TACOS: TESS AM CVn Outbursts Survey

Abstract: Using TESS we are doing a systematic study of outbursting AM CVn systems to place some limits on the current outbursts models. We present the TESS light curve (LC) for 9 AM CVns showing both superoutbursts (SOs) and normal outbursts (NOs). The continuous coverage of the outbursts with TESS allows us to place stringent limits on the duration and structures of the SOs and the NOs. We present evidence that in at least some of the systems enhanced mass transfer (EMT) has to be taken into account to explain the obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…The bottom panels shows the most recent data, in which 4 short duration ( 1 day) outbursts which occur very shortly after a superoutburst. These echo outbursts have also been seen in other AM CVn systems (e.g Green et al 2020;Duffy et al 2021;Pichardo Marcano et al 2021…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The bottom panels shows the most recent data, in which 4 short duration ( 1 day) outbursts which occur very shortly after a superoutburst. These echo outbursts have also been seen in other AM CVn systems (e.g Green et al 2020;Duffy et al 2021;Pichardo Marcano et al 2021…”
supporting
confidence: 67%
“…For ZTFJ0407−00, we observe one outburst in the ZTF data, which showed multiple short 'echo' outbursts days to weeks after the main superoutburst, also seen by Green et al (2020), Duffy et al (2021), andPichardo Marcano et al (2021). Well sampled lightcurves of the systems also show a brighter baseline level and up to 20 echo-outbursts after a superoutburst.…”
Section: Outbursts and Accretion Statementioning
confidence: 64%
“…TESS FFIs are yielding significant scientific results despite the limitations in data precision and availability. Cataclysmic variable light curves and supernova light curves may be derived with high precision from FFIs (Vallely et al 2019;Fausnaugh et al 2021;Pichardo Marcano et al 2021). Planet searches and EB searches have been conducted with FFIs, but on a limited scale (Bouma et al 2019;Nardiello et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The Transiting Exoplanet Survey Satellite (TESS) offers nearly complete sky coverage, uniform cadence, and highprecision photometry. This enables a huge amount of timedomain science, from transiting planets (Huang et al 2018;Vanderspek et al 2019), to eclipsing binaries (EBs) (Borkovits et al 2020;Powell et al 2021;Prša et al 2022), to stellar pulsations and variability (Campante et al 2016;Antoci et al 2019;Córsico et al 2019), to exotic binaries with accretion and complex variability (Pichardo Marcano et al 2021;Hernandez et al 2022;Rawat et al 2022), to blazars (Weaver et al 2020;Raiteri et al 2021), and supernova transients (Vallely et al 2019;Fausnaugh et al 2021). The headline TESS science product is its two minute photometry processed with the official Science Processing Operations Center (SPOC) pipeline (Jenkins et al 2016), but this is only available for ∼10 5 stars in each 27 day observed sector.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to searches from individual observations, one can perform a CWDB search with a larger scale. Several surveys can be used to pick potential CWDB candidates, like the Catalina Real-time Transient Survey (CRTS; Breedt et al 2014), the Global Astrometric Interferometer for Astrophysics (Gaia; Geier et al 2017;El-Badry et al 2021a;Gentile Fusillo et al 2021;Rebassa-Mansergas et al 2021;Torres et al 2022), the Optical Gravitational Lensing Experiment (Wevers et al 2016), the Palomar Transient Factory (van Roestel et al 2017(van Roestel et al , 2018Burdge et al 2019b), the All Sky Automated Survey for SuperNovae (Rivera Sandoval et al 2022), the Transit Exoplanet Survey Satellite (Wang et al 2020;Pichardo Marcano et al 2021;Hernandez et al 2022), the Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST; Wang et al 2022b), and most recently the Zwicky Transient Facility (ZTF; Burdge et al 2020aBurdge et al , 2020bCoughlin et al 2020;Ofek et al 2020;Szkody et al 2020;Kupfer et al 2021;Szkody et al 2021;Keller et al 2022;McWhirter & Lam 2022). Repeated observations of the same sources can reveal optical variability, and some of these surveys can be used, and have been used, to determine the periodicity.…”
Section: Introductionmentioning
confidence: 99%